Long non-coding RNAs play an important regulatory role in tumorigenesis and tumor progression through aerobic glycolysis - Fan, Ni; Fu, Hui; Feng, Xuchen; Chen, Yatong; Wang, Jingyu; Wu, Yuqi; Bian, Yuhong; Li, Yingpeng (Frontiers in Molecular Biosciences, 2022)
Compared to normal cells, cancer cells generate ATP mainly through aerobic glycolysis, which promotes tumorigenesis and tumor progression. Long non-coding RNAs (LncRNAs) are a class of transcripts longer than 200 nucleotides with little or without evident protein-encoding function. LncRNAs are involved in the ten hallmarks of cancer, interestingly, they are also closely associated with aerobic glycolysis. However, the mechanism of this process is non-transparent to date. Demonstrating the mechanism of lncRNAs regulating tumorigenesis and tumor progression through aerobic glycolysis is particularly critical for cancer therapy, and may provide novel therapeutic targets or strategies in cancer treatment. In this review, we discuss the role of lncRNAs and aerobic glycolysis in tumorigenesis and tumor progression, and further explore their interaction, in hope to provide a novel therapeutic target for cancer treatment.